The Immunomodulatory Functions of Diacylglycerol Kinase ζ - Singh, Brenal K.; Kambayashi, Taku (Frontiers in Cell and Developmental Biology, 2016)
The generation of diacylglycerol (DAG) is critical for promoting immune cell activation, regulation, and function. Diacylglycerol kinase ζ (DGKζ) serves as an important negative regulator of DAG by enzymatically converting DAG into phosphatidic acid (PA) to shut down DAG-mediated signaling. Consequently, the loss of DGKζ increases DAG levels and the duration of DAG-mediated signaling. However, while the enhancement of DAG signaling is thought to augment immune cell function, the loss of DGKζ can result in both immunoactivation and immunomodulation depending on the cell type and function. In this review, we discuss how different immune cell functions can be selectively modulated by DGKζ. Furthermore, we consider how targeting DGKζ can be potentially beneficial for the resolution of human diseases by either promoting immune responses important for protection against infection or cancer or dampening immune responses in immunopathologic conditions such as allergy and septic shock.